2016
DOI: 10.7554/elife.14470
|View full text |Cite
|
Sign up to set email alerts
|

PROP1 triggers epithelial-mesenchymal transition-like process in pituitary stem cells

Abstract: Mutations in PROP1 are the most common cause of hypopituitarism in humans; therefore, unraveling its mechanism of action is highly relevant from a therapeutic perspective. Our current understanding of the role of PROP1 in the pituitary gland is limited to the repression and activation of the pituitary transcription factor genes Hesx1 and Pou1f1, respectively. To elucidate the comprehensive PROP1-dependent gene regulatory network, we conducted genome-wide analysis of PROP1 DNA binding and effects on gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 58 publications
0
54
0
2
Order By: Relevance
“…In support of this idea, we discovered that Prop1 is transiently co-expressed with Sox2 in embryonic pituitary development, and using Prop1 mutant mice we showed that Prop1 is required for initial establishment of adequate stem cell pools, as well as for normal stem cell colony forming behavior (11). Prop1 mutant neonates have more SOX2-positive cells than wild-types, and they remain in the marginal zone (Figure 4).…”
Section: Epithelial-to-mesenchymal Transition (Emt) Events In Pituitamentioning
confidence: 90%
See 3 more Smart Citations
“…In support of this idea, we discovered that Prop1 is transiently co-expressed with Sox2 in embryonic pituitary development, and using Prop1 mutant mice we showed that Prop1 is required for initial establishment of adequate stem cell pools, as well as for normal stem cell colony forming behavior (11). Prop1 mutant neonates have more SOX2-positive cells than wild-types, and they remain in the marginal zone (Figure 4).…”
Section: Epithelial-to-mesenchymal Transition (Emt) Events In Pituitamentioning
confidence: 90%
“…This tissue is thought to be the stem cell niche and is referred to as the marginal zone. There is an EMT-like transition, including a reduction in E-cadherin expression at the ventral aspect of the Rathke’s cleft, as anterior lobe progenitor cells begin to differentiate and delaminate ventrally and migrate laterally from the lumen, causing the expansion of the parenchyma of the anterior lobe (11,31,32). …”
Section: Pituitary Organogenesis: Formation Of the Mature Gland From mentioning
confidence: 99%
See 2 more Smart Citations
“…The localisation of PROP1 marks a proportion of SOX2+ cells that are able to form colonies in vitro, but this was shown to be required for enabling transition to the progenitor state and for leaving the epithelium via epithelial-mesenchymal transition [32]. SOX9+ cells (also expressing SOX2) do generate functional cells of all lineages in vivo [21], but the difference in potential between single SOX2+ only and double SOX2;SOX9 is not yet known, neither is the functional requirement for SOX9.…”
Section: Pituitary Stem Cells Are Contained Within the Sox2+ Populationmentioning
confidence: 99%